Analysis of Consumer Preference for Cassava Products in Akoko South West Local Government Area of Ondo State, Nigeria - Stephen, Ojo Olutope; Oluwatosin, Olofinsao A.; Medinat, Abdulaleem A. (International Journal of Social Sciences Perspectives, 2020)
The study analysed consumer preference for cassava products in Akoko South local Government area of Ondo state, Nigeria. Data were collected from one hundred and ten (110) respondents with the aid of a structured questionnaire. Descriptive statistics and multiple regressions together with correlation Test were used to analyse the study data. The result revealed that the mean age of the household head was found to be 49.5 years and have a mean income of ₦26,800. The result revealed that garri is the major cassava product consumed. The result of the regression revealed that household size and income are the major factor that enhance the consumption of cassava products in the study area. The results of the Pearson Correlation showed that there is no significant relationship between income and the cassava products consumed. The major constraints faced were price of the products, taste, and household size. This research recommends that the Government, Ministries of Agriculture should provide improved technologies for production, processing and adding value to the cassava products. Scientists and bioengineers are encouraged to develop cassava varieties with less cyanide content and healthier for consumption by the old. Extension personnel should provide extensive services for actors of cassava value chain.